Villenave-d’Ornon (Gironde, France): A wreck from the early Middle Ages - Rieth, Eric; Grimbert, Laurent; Guyon, Marc (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
The Villenave-d’Ornon wreck was discovered in 2013 south of Bordeaux, near the Garonne River. Its scientific interest led the DRAC Nouvelle Aquitaine to prescribe a preventive excavation, which was begun by Inrap in 2019. Initial observations indicate a robust boat, keel-built, adapted to transporting goods in coastal areas and riverine environments. Several radiocarbon dates provide a chronology between the second half of the 6th and the end of the 7th century. As the dismantling of the wreck could not be completed in 2019, a second operation is under way until September 2022.